SDG Indicator Codes As Metadata In Institutional Repositories And Scholarly Indexing Systems - Havemann, Johanna (My University, 2023)
To encourage scholarly publishing venues and research institutions in adopting the SDG indicator taxonomy for solution-oriented research output that allows for direct application to societal and environmental interventions to mitigate climate change, forced migration, war and conflict, and other existential crises of our times.
Keywords: SDG Indicator; Scholarly Stakeholders; Institutional Repositories